2015
DOI: 10.5673/sip.53.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Public Participation and the Decision Making Process

Abstract: The implementation of the public participation process is important for the democratisation of social values and better planning and fulfilment of public needs. The public participation process, however, is sometimes threatened by bureaucratic constraints caused by the lack of a systematic approach and an inadequate public administration system, which contribute to the public exclusion from the process. The exclusion is also caused by the lack of knowledge about public participation and low levels of education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Communities can obtain benefit maximally through their participation in developing the programmes. The main goal is to provide the broadest opportunity for the community to contribute to the development process (Marzuki, 2015). The development, which is conducted with community participation is expected to be in line with community aspiration, conformitybased on the capability of local communities, and the communities' commitment.…”
Section: Community Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities can obtain benefit maximally through their participation in developing the programmes. The main goal is to provide the broadest opportunity for the community to contribute to the development process (Marzuki, 2015). The development, which is conducted with community participation is expected to be in line with community aspiration, conformitybased on the capability of local communities, and the communities' commitment.…”
Section: Community Participationmentioning
confidence: 99%
“…The development, which is conducted with community participation is expected to be in line with community aspiration, conformitybased on the capability of local communities, and the communities' commitment. It is important to emphasize that an optimal achievement in development depends on how much participation of all parties, especially community participation, is (Lukić, 2011;Marzuki, 2015). Hastuti et al, (2013) suggested that in developing the tourism sector, active community participation is necessary for the sustainability and preservation of natural resources that are available in the village of tourism.…”
Section: Community Participationmentioning
confidence: 99%
“…A higher degree of citizen participation in decision-making contributes to achieving development results effectively and efficiently. There are two degrees of opportunity to influence any decision, namely before the preparation of the proposal and after the publication of the proposed plan (Marzuki, 2015). As per Marzuki, citizens submit their ideas and suggestions for planning work before the implementation of the plan, while they have another opportunity to submit their objections and amendments, if any, after the proposed plan has been published.…”
Section: Citizen Participation and Development Planningmentioning
confidence: 99%
“…Irvin and Stansbury (2004) argued that participation may take a longer time, lead to higher costs, and increase the probability of improper decisions. Similarly, Marzuki (2015) argued that citizen participation is also time-consuming and sluggish decision-making because citizens need to be briefed and even first be educated to participate meaningfully in administrative processes. Pandeya and Shrestha (2016) found that participatory practices would not only mend planning efficacy but would also create free-rider, ethical hazard problems, new forms of corruption, often relying on individualistic benefits rather than equal and holistic benefits.…”
Section: Citizen Participation and Development Planningmentioning
confidence: 99%
“…También la participación es entorpecida, porque no se conocen las formas de participación de la ciudadanía por el bajo nivel académico de las partes interesadas, actitudes negativas a la participación de parte de los administradores públicos e incluso de las mismas partes interesadas. Se destaca como limitante la estructura legal que no alienta la participación y solo considera a algunos grupos (Marzuki, 2015). Es el caso por ejemplo del diseño de las ciudades que generalmente ha estado en manos de profesionales del diseño urbano, bajo la supervisión de la administración pública, sin la participación ciudadana (Dyer et al, 2017).…”
Section: Decisiones Participativas Y Análisis De Interesadosunclassified